La universidad-empresa en América Central: el caso de la UCR - Caamaño Morúa, Carmen (2020)
This article is based on the analyses of qualitative material from interviews, participant observation, documentary research, and official Central American universities´ web pages, social media, and newspapers. Those show transformations in the model of public university which have taken place in the region since the 1980s. I focus on the University of Costa Rica and compare it to other cases in Nicaragua, Honduras and Panama. I identify actors promoting changes towards a corporative university model, not only through policies in education, but also, through processes of governmentality linked to neoliberal internationalization. These changes prevent the university from assuming care policies to protect students and personnel when confronting attacks from political-entrepreneur sectors or dealing with the Covid-19 crisis´ demands.